2013
DOI: 10.1063/1.4819903
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical properties of energetic ionic liquids/nitric acid mixtures: Insights from molecular dynamics simulations

Abstract: Molecular dynamics (MD) simulations of mixtures of the room temperature ionic liquids (ILs) 1-butyl-4-methyl imidazolium [BMIM]/dicyanoamide [DCA] and [BMIM][NO3(-)] with HNO3 have been performed utilizing the polarizable, quantum chemistry based APPLE&P(®) potential. Experimentally it has been observed that [BMIM][DCA] exhibits hypergolic behavior when mixed with HNO3 while [BMIM][NO3(-)] does not. The structural, thermodynamic, and transport properties of the IL/HNO3 mixtures have been determined from equili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…To a first approximation in these drop tests, the observed ignition delay, τ, may be described by τ = 1/ k experimental = 1/ k mixing + 1/ k reaction where the k ’s are the first-order rate coefficients, and an increase in the mixing rate or in the reaction rate will reduce the observed τ. Moreover, previous nonreactive MD simulations of BMIM + DCA – + HNO 3 indicated that mixing of the two liquids is rapid and can increase the temperature of the mixture due to enthalpy release on mixing . The present Figure observations of Na + addition are consistent with this notion and Vogelhuber’s DFT calculations.…”
Section: Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To a first approximation in these drop tests, the observed ignition delay, τ, may be described by τ = 1/ k experimental = 1/ k mixing + 1/ k reaction where the k ’s are the first-order rate coefficients, and an increase in the mixing rate or in the reaction rate will reduce the observed τ. Moreover, previous nonreactive MD simulations of BMIM + DCA – + HNO 3 indicated that mixing of the two liquids is rapid and can increase the temperature of the mixture due to enthalpy release on mixing . The present Figure observations of Na + addition are consistent with this notion and Vogelhuber’s DFT calculations.…”
Section: Results and Discussionsupporting
confidence: 91%
“…Moreover, previous nonreactive MD simulations of BMIM + DCA − + HNO 3 indicated that mixing of the two liquids is rapid and can increase the temperature of the mixture due to enthalpy release on mixing. 23 The present Figure 1 observations of Na + addition are consistent with this notion and Vogelhuber's DFT calculations.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
“…Simulations were conducted at 333 K. MD simulations utilized the atomistic polarizable APPLE&P force field that has been tuned for description of energetic RTILs and their mixtures with nitric acid. 25 Covalent bond lengths were constrained using the velocity-Verlet form of the SHAKE algorithm. 26 The Ewald summation method was used for treatment of long-range electrostatic forces between partial atomic charges and between partial charges and induced dipoles.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…This approach, utilising the APPLE&P transferrable POL force field, has been shown to successfully model both thermodynamic and dynamic properties for a wide variety of systems, including polymers [45], molecular crystals [49], and ionic liquids [41,46,50]. While we refer to the APPLE&P force field as transferrable, it is not generic in nature.…”
Section: Force Field Developmentmentioning
confidence: 98%